Ograniczenia swobody prowadzenia kampanii wyborczej w świetle regulacji "Kodeksu wyborczego" - Balicki, Ryszard; Piech, Karolina (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
This article concerns limitations, which the legislator levied on entities conducting an election campaign. The authors presented the most important aspects of the legal regulations pertaining to an electoral campaign and electioneering, next they characterized the institution of “election silence”, limitations placed upon the place and time of conducting an electoral campaign and personal limitations, concluded in Polish Electoral Code. The article concludes with proposals of changes, which it would be possible to introduce into Polish election law.
Limitations on the freedom to conduct electoral campaigns in the light of “Electoral Code” regulations
Keywords: electoral campaign; electioneering; Electoral Code; elections; indirect democracy; election silence